Relationship Between Parents Socio Economic Status and Students Interest in Continuing to Vocational High School - Evan Pratama; Mursyid Ridha (Universitas Negeri Padang, 2019)
Vocational high School is a form of secondary education that organizes educational programs that are oriented towards the development of skills in accordance with the vocational field of students. Found, in the field of many students who are interested in continuing education to vocational high school rather than high school, students want to proceed to SMK because they want to work fast and most practice rather than with theory. There are also students who have a perception that vocational graduates can not continue to the college. Interest is a sense of love and interest in something or activity, with no one to tell. One factor that affects interest is the socio-economic status. This research is a correlational descriptive type study with quantitative methods. Sample quantities of 219 students were selected using the Proportional Random Sampling technique. The research instruments used are the social status questionnaire and the student interest questionnaire. The results revealed that (1) the social economic status of students of SMP N 22 Padang is in the low category (2) the interest of students are in the category of interested (3) there is a significant negative relationship between socio-economic status with the interest of students At SMP N 22 Padang. Based on research findings, it is advisable to the school teacher BK/counsellor to provide guidance and counseling services, which are orientation services, information services, placement and distribution services, individual counselling services and Group guidance in order to help students who have problems in their advanced school selection and the economic status of their parents.